2007
DOI: 10.1111/j.1572-0241.2006.01025.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Steatosis in Genotype 4 Chronic Hepatitis C Is Mainly Because of Metabolic Factors

Abstract: Moderate or severe steatosis is significantly less frequent in genotype 4 than 3 chronic hepatitis C patients and similar between genotype 4 and 1. In nondiabetic, nonoverweight patients, moderate or severe steatosis is present in only 10-15% of genotype 4 or 1 compared with 40% of genotype 3 patients. Thus, hepatic steatosis in genotype 4 is mostly associated with metabolic factors, similar to those in genotype 1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
20
0
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 29 publications
7
20
0
5
Order By: Relevance
“…This is comparable to findings from Tsochatzis et al [10] who found that moderate to severe steatosis was more frequent in genotypes 3 than 4, but was similar between genotypes 1 and 4. On the other hand, Reddy et al [11] found that steatosis was more prevalent in genotype 3 than other genotypes.…”
Section: Discussionsupporting
confidence: 94%
“…This is comparable to findings from Tsochatzis et al [10] who found that moderate to severe steatosis was more frequent in genotypes 3 than 4, but was similar between genotypes 1 and 4. On the other hand, Reddy et al [11] found that steatosis was more prevalent in genotype 3 than other genotypes.…”
Section: Discussionsupporting
confidence: 94%
“…In this setting, IR is either virus-mediated or due to host metabolic factors such as visceral obesity [44] . A similar association has been shown for genotype 4 [45] . In contrast, steatosis in HCV genotype 3 infection is predominantly a direct effect of the virus, occurring in the absence of other metabolic risk factors [46,47] .…”
Section: Complications Of Hcv-induced Irsupporting
confidence: 66%
“…The degree of steatosis in this genotype is independent of the HCV viral load, and antiviral therapy does not improve steatosis in these patients. Similar data have been obtained for genotype 4 infection, whereas few data are available for genotype 2 [263] . The presence of HCV infection in patients with DM may also increase the proportion of DM-related chronic nephrologic complications [86,264] .…”
supporting
confidence: 64%